Screening of proper leaf size in Centella asiatica for antioxidant potential and separation of phenolics using RP-HPLC - Ritisha N. Tatmiya, Kiran S. Chudasama, Vibhuti M. Jhala and Vrinda S. Thaker (Journal of Applied Pharmaceutical Science, 2014)
Centella asiatica is a valuable medicinal plant with abundant amount of pharmaceutically useful compounds; however, it is important to know the proper physiological age for drug formulation. In the present study, smaller to larger thirteen groups of Centella asiatica leaves were evaluated for growth, chlorophyll content and antioxidant activity. The growth was measured in the terms of leaf area, fresh and dry weights and water content. Maximum antioxidant activity was found in third size group of the leaf which was further analyzed for phenolics in RP-HPLC. The probable role of these phenols in antioxidant activities is discussed.
Keywords: Centella asiatica, growth, chlorophyll content, antioxidant activity and phenolics.